Comparison between absorbable pins and mini-screw fixations for the treatment of radial head fractures Mason type II-III - Tarallo, Luigi (BMC Musculoskelet Disord, 2018)
BACKGROUND: The treatment of comminuted radial head fractures can include prosthetic replacement or open reduction and internal fixation. The purpose of this study is to evaluate the results of two different internal fixation systems for Mason type II-III radial head fractures. METHODS: Between 2005 and 2015, 82 patients were treated using pins and 65 patients by mini-screws. The follow-up protocol included: a clinical evaluation 15 days after surgery, and clinical and radiographic evaluations performed at 30 and 60 day intervals, unless any complications were reported by the patient. Over a period of at least 12-months of follow-up, patients were checked and interviewed. Clinical examinations included elbow range of motion (ROM), arm, shoulder and hand Disabilities, (DASH), and the Mayo Elbow Performance Score (MEPS). RESULTS: Sixty-one subjects who had been treated with mini-screws were clinically reviewed at a mean 47.3 ± 35.8 month of follow-up; all patients who had been treated using absorbable pins were evaluated at a mean 82.5 ± 20.6 month of follow-up. No significant statistically differences were observed between the two groups in the mean ROM, DASH, and MEPS scores. Residual pain was reported in 15.8%of the patients treated by pins and 9.2% patients treated by mini-screws. Secondary displacement of fracture fragments was observed in 8.5% patients treated by pins and 1.6% using mini-screws. CONCLUSIONS: Both absorbable pins and mini-screws provided adequate strength and rigidity, allowing good clinical and functional scores at a mid-term follow-up. However, a higher rate of secondary displacement of the fracture fragments was reported among subjects who had been treated using absorbable pins.